Student engagement as a function of environmental complexity in high school classrooms. (June 2016) - Shernoff, David J.; Kelly, Sean; Tonks, Stephen M.; Anderson, Brett; Cavanagh, Robert F.; Sinha, Suparna; Abdi, Beheshteh
Abstract: The purpose of this study was to investigate the linkage between the quality of the learning environment and the quality of students' experience in seven high school classrooms in six different subject areas. The quality of the learning environment was conceptualized in terms of environmental complexity, or the simultaneous presence of environmental challenge and environmental support. The students ( N = 108) in each class participated in the Experience Sampling Method (ESM) measuring their engagement and related experiential variables. Concurrently, environmental complexity and its subdimensions were observed and rated from video with a new observational instrument, The Optimal Learning Environments – Observational Log and Assessment (OLE-OLA). Using two-level HLM regression models, ratings from the OLE-OLA were utilized to predict student engagement and experiential variables as measured by the ESM. Results showed that environmental complexity predicted student engagement and sense of classroom self-esteem. Implications for research, theory and practice are discussed. Highlights: We investigate the linkage between the learning environment and student engagement. High school students were observed and completed the Experience Sampling Method. Environmental complexity accounted for variation in engagement and classroom self-esteem. Engaging learning environments were characterized by combined challenges and supports.